Characteristics and outcome of patients with therapy-related acute promyelocytic leukemia front-line treated with or without arsenic trioxide - Kayser, Sabine; Benner, Axel; Krämer, Alwin; Ho, Anthony Dick; Schlenk, Richard Friedrich (Leukemia, 2017)
Therapy-related acute promyelocytic leukemia (t-APL) is relatively rare, with limited data on outcome after treatment with arsenic trioxide (ATO) compared to standard intensive chemotherapy (CTX). We evaluated 103 adult t-APL patients undergoing treatment with all-trans retinoic acid (ATRA) alone (n=7) or in combination with ATO (n=24), CTX (n=53), or both (n=19). Complete remissions were achieved after induction therapy in 57% with ATRA, 100% with ATO/ATRA, 78% with CTX/ATRA, and 95% with CTX/ATO/ATRA. Early death rates were 43% for ATRA, 0% for ATO/ATRA, 12% for CTX/ATRA and 5% for CTX/ATO/ATRA. Three patients relapsed, two developed therapy-related acute myeloid leukemia and 13 died in remission including seven patients with recurrence of the prior malignancy. Median follow-up for survival was 3.7 years. None of the patients treated with ATRA alone survived beyond one year. Event-free survival was significantly higher after ATO-based therapy (95%, 95% CI, 82-99%) as compared to CTX/ATRA (78%, 95% CI, 64-87%; P=0.042), if deaths due to recurrence of the prior malignancy were censored. The estimated 2-year overall survival in intensively treated patients was 88% (95% CI, 80-93%) without difference according to treatment (P=0.47). ATO when added to ATRA or CTX/ATRA is feasible and leads to better outcomes as compared to CTX/ATRA in t-APL.
Gesehen am 30.07.2018